PENGARUH KEPUASAN KERJA DAN KEPEMIMPINAN YANG MELAYANI TERHADAP ORGANISASIONAL CITIZENSHIP BEHAVIOR DAN DAMPAKNYA TERHADAP KOMITMEN ORGANISASI (Studi di Dinas Kebersihan dan Pertamanan Kota Semarang) - Adwin Pri Ardanto, 1342020024 (Jurnal Mahasiswa Pasca Sarjana, 2015)
This research is a study that tested the effect of job satisfaction and serve leadership to organizational citizenship and its impact on organizational commitment in the Dinas Kebersihan dan Pertamanan Semarang. This research has been tested on the respondents who work in the Dinas Kebersihan dan Pertamanan Semarang as an employee, using SPSS Statistics Test. This study describes the results of job satisfaction and leadership serve effect on organizational citizenship, servant leadership, job satisfaction and organizational citizenship affect the organization commitment. Organizatioanl citizenshipÂ behavior can not mediate job satisfaction and serve leadership to organizational commitment as the coefficient of mediation is smaller than the direct effect of both on job satisfaction and serve leadership to organizational commitment. Keywords: job satisfaction, serve leadership, Organizational citizenship behavior, organizational commitment